Amphisbaena mensae Catro-Mello, 2000 is a synonym of Amphisbaena talisiae Vanzolini, 1995 (Squamata: Amphisbaenia: Amphisbaenidae) - Costa, Henrique C.; Graboski, Roberta; Zaher, Hussam (Zootaxa, 2019)
Amphisbaena talisiae and A. mensae, two worm lizard species endemic to the Cerrado ecoregion, in central Brazil, are considered synonyms based on morphological characters. With the proposed synonymy, the name A. talisiae has priority of use over A. mensae. Amphisbaena talisiae can be distinguished from its congeners by a series of morphological characters, including a round head, three supralabial and three infralabial scales, postmalar row absent, four precloacal pores without a median hiatus, 205–234 body annuli, 17–29 caudal annuli, 10–14 dorsal and 14–18 ventral segments in a midbody annulus. The species is recorded from southeastern Mato Grosso, eastern Minas Gerais and central Tocantins states in central Brazil, and its conservation status should be changed from Data Deficient to Least Concern.